Development of an indirect ELISA for the detection of venezuelan equine encephalitis virus specific antibodies in horses - Manon Chevrier; Laure Mathews-Martin; Teheipuaura Mariteragi-Helle; Marine Dumarest; Yasmine Boudjadi; Emmanuel Bréard; Mathilde Turpaud; Thomas Deshayes; María Aldana Vissani; Rommel Lenin Vinueza; Roberto Coello Peralta; Jessica Vanhomwegen; et al. (PLoS ONE, 2026)
Venezuelan equine encephalitis virus (VEEV) is a re-emerging zoonotic pathogen to which equines are most susceptible mammals hosts with a high mortality rate raging from19 to 83%. The virus, transmitted between vertebrates and mosquitos, causes unpredictable sporadic epizootic outbreaks in equids and humans across Central and South America. Although VEEV is not currently circulating in Europe the combination of global change, increasing international trade and the presence of potentially competent vectors (mosquitoes of the genera Aedes and Culex ), raises a non-negligible risk of its introduction. In response, the European Commission mandated the European Union Reference Laboratory (EURL) for equine diseases to establish an easy-to-implement and fast serological method for detecting VEEV infection in horses. The study aimed to develop a sensitive and specific in-house indirect enzyme-linked immunosorbent assay (ELISA) based on the E2 glycoprotein of VEEV. The assay was evaluated using 469 samples from non-infected horses, naturally infected horses (with VEEV and/or eastern equine encephalitis virus (EEEV) and/or western equine encephalitis virus (WEEV)), and horses vaccinated against EEEV/WEEV. The ELISA demonstrated robust diagnostic performance with a sensitivity of 97.3% and a specificity and 93.8%. This assay is therefore an easy-to-implement diagnostic method, offering an alternative to virus neutralization. It is suitable for sero-epidemiological studies to accurately determine the distribution of VEEV in the America and to monitor potential introduction of the virus in new area, includingEurope.